P17.05.A Re-irradiation with bevacizumab for large volume chemo-refractory glioblastoma after prior high-dose chemoradiotherapy. (5th September 2022) - Horsley, P; Tong, E; Wheeler, H; Venkatesha, V; Chan, J; Kastelan, M; Back, M
Abstract: Background: There are limited options for salvage treatment of glioblastoma. The role of re-irradiation (reRT) for large-volume chemo-refractory relapse is not established due to concerns regarding potential toxicity, which may be overcome with use of bevacizumab. Material and Methods: Patients who received initial post-operative chemoradiotherapy with 60Gy (EORTC-NCIC protocol) for glioblastoma across two centres from 2007-2021 were entered into a prospective database. Patients with progressive chemo-refractory disease, including some progressing on bevacizumab, were considered for reRT. Pseudoprogression and late RT necrosis was actively excluded using sequential MRI and PET. Clinico-pathologic characteristics of the reRT cohort and patients who had progressed but did not undergo reRT were compared. Kaplan-Meier survival analysis was used to assess overall (OS) and progression-free survival (PFS) from diagnosis in the overall and reRT cohorts as well as OS post-reRT. Factors associated with improved survival post-reRT were assessed. Results: Of 447 patients treated for glioblastoma, 372 had progressed of which 71 received reRT. Median follow up for surviving patients was 26 and 37 months from diagnosis for the reRT and overall cohorts respectively. Median PFS and OS from initial diagnosis were 11.6 (95% CI: 9.4-14.2) and 23.6 (95% CI: 21.0-33.1) months respectively for re-RT patients, compared to 11.8 (95% CI: 11.0-12.5) and 18.0 (95% CI 17.0-19.1) months for the overall cohort. The reRT subgroup were more likely to be younger (median 53 vs. 59 years, p<0.001), have ECOG performance status at diagnosis 0-1 (86% vs. 69%, p=0.002) and have MGMT promoter methylation (54% vs. 40% p=0.083). There was no difference in extent of initial resection (p=0.59). The most common reRT schedule was 15 fractions to a total dose of either 40 Gy (32 patients) or 35 Gy (28 patients). Sixty (85%) had progression on bevacizumab prior to reRT; bevacizumab was continued during reRT in these cases. A further 10 (14%) received salvage bevacizumab after reRT. Median reRT PTV volume was 135cc (IQR 69-207cc). Median OS following reRT was 7.1 months (95% CI: 6.3-7.9). Six (8%) patients were admitted to hospital within 30 days of reRT, only one due to reRT toxicity. Median OS post-reRT was 7.7, 6.4 and 6.0 months for patients aged <50, 50-70 and >70 years respectively (p=0.021) and 8.1 vs. 6.3 months for patients with ECOG performance status of 0-1 and 2-3 respectively (p=0.039). Distant versus local progression (p=0.87), anatomical location of disease (p=0.65), MGMT methylation status (p=0.77) and PTV volume (p=0.91) did not predict post-reRT survival. Conclusion: Large volume reRT for patients with recurrent glioblastoma is feasible, well-tolerated, associated with favourable overall survival and produces meaningful post-radiotherapy survival times.